ACUTE ANKLE SPRAIN INJURY ALTERS KINEMATIC AND CENTRE OF PRESSURE MEASURES OF POSTURAL CONTROL DURING THE STAR EXCURSION BALANCE TEST. Issue 7 (11th March 2014) - Doherty, C; Delahunt, E; Bleakley, C; Hertel, J; Ryan, J; Caulfield, B
Abstract : Background: Postural control assessments are frequently used in clinical and research settings to evaluate movement deficits following acute lateral ankle sprain (LAS). The Star Excursion Balance Test (SEBT) is one such postural control assessment tool. To date, no research has investigated the immediate post-injury movement strategies associated with LAS, as quantified by center of pressure (COP) and kinematic analyses during performance of selected reach directions of the SEBT. Objective: To compare the kinematic and COP patterns of a group with acute LAS and a non-injured control group during performance of selected reach directions of the SEBT. Design: Cross-sectional. Setting: University biomechanics laboratory. Participants: 81 participants with acute LAS and 19 non-injured controls. Main outcome measures: 3D kinematics of the hip, knee and ankle joints as well as associated fractal dimension (FD) of the COP path during the performance of the anterior (ANT), posterior-lateral (PL) and posterior-medial (PM) reach directions of the SEBT. Results: The LAS group had bilateral decreased reach distances normalised to leg length in the ANT, PL and PM reach directions of the SEBT compared to non-injured control participants (P<.05). The LAS group were also characterized by altered temporal sagittal plane kinematic profiles at the hip, knee and ankle joints of their injured and non-injured limbs for each of the reach directions of the SEBT, compared to the control group (P<.05). This altered kinematic profile was associated with a reduced FD of the COP path for each reach direction on the involved limb only (P<.05). Conclusion: Acute LAS is associated with bilateral deficits in postural control, evidenced by reduced angular displacements of the hip, knee and ankle joints, as well as reduced reach distances and FD of the COP path during the performance of a dynamic postural control assessment task.